ANALYSIS OF THE FACTORS AFFECTING DEVELOPMENT OF THE MUTUAL FUNDS IN RUSSIA - Alexander V. Revinsky (Статистика и экономика, 2016)
N this paper, we scrutinize the actual factors, reverberating dynamics of the mutual funds in Russia. Based on the example of risk premium analysis and study of investment strategies, we show, why investors are not in a hurry to invest in assets on Russian market. We believe it to be attributed to the general risk aversion of investors